Moral animals ideals and constraints in moral theory - Wilson, Catherine 1951- (Clarendon Press Oxford University Press, 2004)
"In Moral Animals, Catherine Wilson develops a theory of morality based on two fundamental premises: first, that moral progress implies the evolution of moral ideals involving restraint and sacrifice; second, that human beings are outfitted by nature with selfish motivations, intentions, and ambitions, that place constraints on what morality can demand of them. Formative claims, she goes on to show, can be understood as projective hypotheses concerning the conduct of realistically-described nonideal agents in preferred fictional worlds. Such claims differ from empirical hypotheses, insofar as the cannot be verified by observation and experiment.